Harmony - Schenker, Heinrich 1868-1935; Jonas, Oswald; Borgese, Elisabeth Mann (Chicago The University of Chicago Press, 1980)
Harmony, Heinrich Schenker's first published work, originally appeared in German in 1906 as "New Musical Theories and Phantasies, by an Artist." Its unusual title indicates what was to be the rationale of Schenker's lifework, that artistic problems call for artistic solutions. Schenker's dedication to the formulation of a complete musical theory above the commonplace theoretical discussions was, in essence, his quest for a pattern in nature for music as art. Schenker's theory draws upon a profound understanding of the works of the masters and every proposition is illustrated by a living musical example.